ห้องเรียนสร้างผู้นำ 360 องศา: กระบวนการสร้างทักษะการเรียนรู้ในศตวรรษที่ 21 ของนักศึกษามหาวิทยาลัยกรุงเทพ - สุภานันท์, ศุภมณฑา (Area Based Development Research Journal, 2016)
การศึกษาการออกแบบการเรียนรู้ การจัดกระบวนการเรียนรู้ และประสบการณ์การเรียนรู้ของนักศึกษาจากโครงการ “การพัฒนาผู้นําการสื่อสารเชิงสร้างสรรค์ 360 องศา เพื่อการปฏิรูปสังคม รุ่นที่สอง ของมหาวิทยาลัยกรุงเทพ” เป็นงานวิจัยเชิงคุณภาพ (Qualitative research) ที่ใช้กระบวนการของการวิจัยเชิงปฏิบัติการ (Action research) เพื่อศึกษาการออกแบบกระบวนการเรียนรู้ การจัดกระบวนการเรียนรู้ และประสบการณ์การเรียนรู้ของนักศึกษา มุ่งเน้นการทําความเข้าใจ การอธิบาย การตีความ และสร้างประสบการณ์การเรียนรู้ร่วมกันระหว่างผู้เรียนและทีมผู้จัดกระบวนการเรียนรู้ โดยมีขั้นตอนที่สําคัญในการศึกษา ได้แก่ การวางแผน (Plan) การลงมือปฏิบัติ (Action) การสังเกต/การเก็บข้อมูล (Observation) และการสะท้อนผลการปฏิบัติ (Reflection) ผลการศึกษาพบว่ามีการใช้กระบวนการและเครื่องมือที่หลากหลาย เพื่อออกแบบการเรียนรู้ เปิดโอกาสให้ผู้เรียนมีส่วนร่วม การจัดกระบวนการเรียนรู้ เริ่มต้นด้วยกิจกรรมค่าย ละลายพฤติกรรม ให้ผู้เรียนได้ย้อนกลับมาทบทวนตนเอง รู้จักตนเอง รู้จักเพื่อน ตามด้วยการให้ผู้เรียนได้สัมผัสโจทย์การเรียนรู้จากพื้นที่จริง พบบุคคลต้นแบบ ผู้นําทางสังคม นักปราชญ์ของชุมชน เชื่อมต่อโลกในห้องเรียนเข้ากับพื้นที่ชุมชน เรียนรู้ประเด็นทางสังคม ประสบการณ์การเรียนรู้ที่นักศึกษาได้รับคือการพัฒนาความเป็นผู้นําร่วม (Collective leadership) การทํางานเป็นทีม รวมไปถึงการพัฒนาทักษะด้านการสื่อสาร และเปิดโลกทางความคิดให้กับผู้เรียนคํานึงถึงประเด็นปัญหาทางสังคมผ่านการทําโครงการธุรกิจเพื่อสังคม 360 Degrees Leadership Development Classroom: The Learning Process of Bangkok University Students in the 21st Century The qualitative research under the second installment of the “360 Degrees Creativity-Oriented Development of Communication Leaders for Social Reform” Project by Bangkok University is focused on the use of action research approach for learning design, learning process management and students’ learning experience. It attempts to understand, explain, interpret and create a joint learning experience between the learners and the learning process management team members. The key stages are planning, action, observation and reflection. It is discovered from the study that a diverse range of processes and tools are used in the learning design effort. This allows the learners to take part in the learning management process. It begins with ice-breaking activities to give the camp members the chance to reflect on themselves and to know their peers better. Subsequently, the learners are exposed to actual learning environments in the field. In the process, they meet model individuals, social leaders and local wise men; create a bridge between the classrooms and the communities; and, familiarize themselves with relevant social particularities. The experience gained enables the students to develop collective leadership, teamwork and communication skills, as well as to gain insights into those social issues through involvement in socially beneficial business programs.